2021
DOI: 10.1029/2021gc010081
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Magnetofossils on Paleointensity Estimations Inferred From Principal Component Analyses of First‐Order Reversal Curve Diagrams for Sediments From the Western Equatorial Pacific

Abstract: Information on geomagnetic paleointensity is fundamentally important for better understanding of the behavior and mechanism of the geodynamo, and marine sediments potentially provide continuous records

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…The difference in these contributions is greater in the deeper part of the core, where biogenic magnetite in the high‐coercivity window contributes up to 40% of the total remanent magnetization. The relative proportion of biogenic magnetite that we calculated should be considered as a minimum estimate because magnetosomes in multistranded configurations and in bent or fold‐collapsed chains can yield vertical spreads that are nearly symmetrical around the central ridge in FORC diagrams (Amor et al., 2022; Berndt et al., 2020; Chang et al., 2019; Inoue et al., 2021; Li et al., 2012; Usui & Yamazaki, 2021), which is counted as the terrigenous component in our calculation. The relative contributions of biogenic magnetite to the remanent magnetization in both coercivity windows increase with depth, which is consistent with the downcore k ARM /SIRM increase, and indicates an increasing relative abundance of biogenic magnetite.…”
Section: Results and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in these contributions is greater in the deeper part of the core, where biogenic magnetite in the high‐coercivity window contributes up to 40% of the total remanent magnetization. The relative proportion of biogenic magnetite that we calculated should be considered as a minimum estimate because magnetosomes in multistranded configurations and in bent or fold‐collapsed chains can yield vertical spreads that are nearly symmetrical around the central ridge in FORC diagrams (Amor et al., 2022; Berndt et al., 2020; Chang et al., 2019; Inoue et al., 2021; Li et al., 2012; Usui & Yamazaki, 2021), which is counted as the terrigenous component in our calculation. The relative contributions of biogenic magnetite to the remanent magnetization in both coercivity windows increase with depth, which is consistent with the downcore k ARM /SIRM increase, and indicates an increasing relative abundance of biogenic magnetite.…”
Section: Results and Interpretationmentioning
confidence: 99%
“…In this study, we used a sediment core from the western equatorial Pacific Ocean to investigate the influence of compositional variations in sediments on RPI estimations. Variable relative proportions of biogenic and terrigenous components in sediments can have a considerable influence on the RPI records in sediments (Inoue et al., 2021; Roberts et al., 2012; Yamazaki et al., 2013). Some previous studies have suggested that biogenic magnetite acquires RPI more efficiently than terrigenous magnetite (Chen et al., 2017; Ouyang et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Our micromagnetic simulations suggest that magnetosome elongation would control mainly the coercivity of magnetofossil endmembers (e.g., the proportion of BS and BH coercivity components), while higher proportions of multi-stranded chains would increase non-central ridge contributions to the FORC diagram. In the case of FORC-PCA analyses, this requires two principal components sensitive to the amplitude and the coercivity of the central ridge, respectively, as observed in a magnetofossil-rich sediment core (Figure 8 in Inoue et al, 2021 ), and the space defined by these two principal components is spanned by at least three magnetofossil-related endmembers. Splitting between these endmembers is controlled by the PCA covariance matrix, rather than by physical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the widespread occurrence of living MTB in the topmost ~10–20 cm of the sedimentary column ( Flies et al, 2005 ; Mao et al, 2014 ; Petermann & Bleil, 1993 ) and cell dissolution in the same layer, magnetofossils are expected to contribute to sedimentary records of the Earth magnetic field like other magnetic particles. However, specific differences between the magnetic and mechanical properties of magnetosome chains and other carriers of a natural remanent magnetization (NRM) might affect relative paleointensity records (RPI) of magnetofossil-rich sediments ( A. P. Chen et al, 2017 ; Inoue et al, 2021 ; Larrasoaña et al, 2014 ; Ouyang et al, 2014 ). Although the exact mechanism of NRM acquisition is unknown, it is possible to make some predictions about the influence of chain geometry on the RPI efficiency of magnetofossils on the basis of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Qian et al 145 used FORC-PCA analysis of eastern Mediterranean sediments to demonstrate that elevated magnetofossil abundances occur at oxidation fronts above organic-rich intervals. FORC-PCA is becoming increasingly common for quantifying sedimentary magnetofossil contents in sediments 146 148 . Combining magnetic measurements and TEM or scanning electron microscope (SEM) observations can provide information to identify, characterize and quantify magnetofossils in natural samples (Fig.…”
Section: Introductionmentioning
confidence: 99%